DETERMINATION OF ANALYTICAL CALCULATION ERROR OF MAGNETIC FIELD OF HIGH-VOLTAGE CABLE LINES WITH TWO-POINT BONDED CABLE SHIELDS CAUSED BY NON-UNIFORM CURRENT DISTRIBUTION IN THE SHIELDS - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. To obtain new calculation correlations, determining approximate energy dissipation and electric erosion of massive basic metallic electrodes in the high-voltage high-current air switchboard (HVCAS) of atmospheric pressure, in-use in the bit chain of the high-voltage electrophysics setting (HVES) with the powerful capacity store of energy (CSE). Methodology. Electrophysics bases of technique of high-voltage and large impulsive currents (LIC), scientific and technical bases of development and planning of high-voltage heavy-current impulsive electro-devices, including HVES and powerful CSE, and also methods of measuring in their bit chains of LIC of the microsecond temporal range. Results. On the basis of new engineering approach the results of calculation estimation of excretions energy and electric erosion of massive basic metallic electrodes are resulted in probed HVCAS. New correlations are obtained for the approximate calculation of thermal energy, selected in an impulsive air spark and on the workings surfaces of anode and cathode of HVCAS. It is entered and a new electrophysics concept, touching equivalent active resistance of impulsive air spark, is mathematically certain. New formulas are obtained for the approximate calculation of most depth of single round crater of destruction on the workings surfaces of basic metallic electrodes of HVCAS, and also mass of metal, thrown out magnetic pressure from this crater of destruction on the electrodes of switch for one electric discharge through them powerful CSE HVES. It is shown that the radius of the indicated single crater of destruction is approximately equal to the maximal radius of plasma channel of a spark discharge between a cathode and anode of HVCAS. The executed high-current experiments in the bit chain of HVES with powerful CSE validated row of the got and in-use calculation correlations for the estimation of energy dissipation and electric erosion of metallic electrodes in examined HVCAS. Originality. New engineering approach is developed for the approximate calculation and estimation of energy dissipation and electric erosion of basic metallic electrodes in HVCAS. A formula is firstly got for approximate calculation unchanging in the process of swaying or aperiodic discharge of CSE HVES on the electric loading of active resistance of impulsive air spark between the electrodes of probed HVCAS. Practical value. Drawing on the got results in a high-voltage impulsive technique provides operative implementation of calculation of balance of electric energy in the high-current circuit of HVES with powerful CSE and point electric load, and also prognostication of the technical state of workings surfaces of massive basic metallic electrodes of HVCAS.